ANALYSIS OF RAW MATERIAL INVENTORY CONTROL FOR FRESH FRUIT BUNCHES (FFB) USING THE EOQ METHOD AT PT. PADASA ENAM UTAMA KOTO KAMPAR HULU DISTRICT - Elen Novita; Suarni Norawati; Litra Diantara (STIE Bangkinang Publishing, 2020)
This study aim to determine the analysis of raw material inventory control for Fresh Fruit Bunches (FFB) using the EOQ method at the PT. Padasa Enam Utama Koto Kampar Hulu District. This research was conducted at the PT. Padasa Enam Utama which is located on Koto Kampar Hulu Distric, Kampar Regency, Riau with a research time of two months, namely in Agustus and September 2020 year. The types and sources of data in this study are primary data and secondary data, while the techniques and data collection conducted by the author in this study are by using observation, interviews and research files. The data analysis method used in this researc is quantitative analysis using the EOQ method through the stages, namely determining the optimal amount of raw material purchases, calculating the optimal purchase frequency, determining the optimal total rawa material inventory and calculating the re-order point. Based on results of the analysisis, it is know that the supply of FFB raw materials using the EOQ method is proven to be more effective and efficient than the supply of FFB rawa materials based on conventional policies that have been implemented by the management of PMKS PT. Padasa Enam Utama Koto Kampar Hulu District. Other than that, by using the EOQ method, the management at PMKS PT. Padasa Enam Utama Koto Kampar Hulu District will also be able to find out when to place the re-order point.